The GALAH survey and Gaia DR2: (non-)existence of five sparse high-latitude open clusters - Kos, Janez; de Silva, Gayandhi; Buder, Sven; Bland-Hawthorn, Joss; Sharma, Sanjib; Asplund, Martin; D’Orazi, Valentina; Duong, Ly; Freeman, Ken; Lewis, Geraint F.; Lin, Jane; Lind, Karin; et al. (Monthly notices of the Royal Astronomical Society, 2018)
Sparse open clusters can be found at high galactic latitudes where loosely populated clusters are more easily detected against the lower stellar background. Because most star formation takes place in the thin disc, the observed population of clusters far from the Galactic plane is hard to explain.We combined spectral parameters from the GALAH survey with the Gaia DR2 catalogue to study the dynamics and chemistry of five old sparse high-latitude clusters in more detail.